2021
DOI: 10.3389/fmed.2021.628021
|View full text |Cite
|
Sign up to set email alerts
|

Low-Load Unilateral and Bilateral Resistance Training to Restore Lower Limb Function in the Early Rehabilitation After Total Knee Arthroplasty: A Randomized Active-Controlled Clinical Trial

Abstract: Background: Continuous passive motion (CPM) is frequently used during rehabilitation following total knee arthroplasty (TKA). Low-load resistance training (LLRT) using continuous active motion (CAM) devices is a promising alternative. We investigated the effectiveness of CPM compared to LLRT using the affected leg (CAMuni) and both legs (CAMbi) in the early post-operative rehabilitation. Hypotheses: (I) LLRT (CAMuni and CAMbi) is superior to CPM, (II) additional training of the unaffected leg (CAMbi) is more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
5
1
Order By: Relevance
“…Training the 11-year-old volleyball player unilaterally and bilaterally and combining the two exercises, found that the results varied. 13 of the 21 performance indicators showed significantly greater changes after 6 weeks of training when unilateral and lateral training were combined, compared to 6 and 3 for unilateral and bilateral training, respectively (Eliassen et al, 2018;Jacksteit et al, 2021;Ramirez-Campillo et al, 2018). To significantly improve performance during high-intensity, short-term explosive activity, a combination of these two exercises would be more beneficial (Gonzalo-Skok et al, 2019;Sun et al, 2018).…”
Section: Unilateral and Bilateral Trainingmentioning
confidence: 98%
“…Training the 11-year-old volleyball player unilaterally and bilaterally and combining the two exercises, found that the results varied. 13 of the 21 performance indicators showed significantly greater changes after 6 weeks of training when unilateral and lateral training were combined, compared to 6 and 3 for unilateral and bilateral training, respectively (Eliassen et al, 2018;Jacksteit et al, 2021;Ramirez-Campillo et al, 2018). To significantly improve performance during high-intensity, short-term explosive activity, a combination of these two exercises would be more beneficial (Gonzalo-Skok et al, 2019;Sun et al, 2018).…”
Section: Unilateral and Bilateral Trainingmentioning
confidence: 98%
“…The domain "selection of reported result" scored best, with 32 articles (92%) scoring "low RoB" [32-36, 38-47, 49-60, 63, 64, 66-68]. By contrast, the domain "deviations from the intended process" scored as "low RoB" in only 24% of the studies [41,44,51,55,56,61,62,65,68]. In total, three articles (8%) [51,56,68] achieved an overall low RoB score.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…The 6-min walk test (6MWT) [33-35, 42, 43, 52, 55, 60] and the Timed Up and Go test (TUG) [33, 41, 44, 51, 58-60, 62, 64] were used in most studies to measure functional performance. Other studies measured and reported functional performance using subjects' maximal walking speed [38,39,49,51,59,64], the stair-climbing test [33,35,42,44,49,60,67], single-leg stance test [38, 49-51, 56, 60, 67, 68], figure-of-eight test [35,42,67,68], functional reach test [58,59], 10-min walk test [41,50,62], 30-s chair test [42,44,60], Berg balance scale [45,58], and subjects' step cadence [49,66]. The 50-foot walking test was reported in one article [36].…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations